Analysis of the Implementation of Financial Accounting Standards for Micro, Small and Medium Entities in Preparing Medan MSME Financial Reports - Khairunnisa, Khairunnisa; Muliyani, Muliyani (SEIKO : Journal of Management & Business, 2024)
This research was conducted on several MSMEs in Medan City. The purpose of this research is to find out whether there is or not and whether or not the MSME financial reports are in accordance with the profit and loss report, financial position report and notes report on financial reports according to EMKM SAK. This research uses quantitative research methods with a descriptive design. The aim of this descriptive research is to create systematic, factual and accurate descriptions, images or paintings regarding the facts, properties and relationships between the phenomena being investigated. Data collection used in this research used field research methods by collecting data about objects at the research location, such as observation, interviews and documentation. It was taken through the Medan City Cooperatives and MSMEs Service and only took MSMEs engaged in the trade sector. Based on the findings, of the 58 MSMEs studied, only 25 have implemented SAK EMKM financial reports or 3.448% of business actors have prepared financial reports in accordance with SAK EMKM. For several MSMEs in Medan City, they do not make financial reports that comply with SAK EMKM due to limited knowledge in applying these financial reports.